Regulated expansion of electricity transmission networks: The effects of fluctuating demand and wind generation - Wolf-Peter Schill; Juan Rosellón; Jonas Egerer (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
We study the performance of different regulatory approaches for the expansion of electricity transmission networks in the light of realistic demand patterns and fluctuating wind power. In particular, we are interested in the relative performance of a combined merchant-regulatory mechanism compared to a cost-based and a merchant-like approach. In contrast to earlier research, we explicitly include both an hourly time resolution and fluctuating wind power, which allows representing demand in a very realistic way. This substantially increases the real-world applicability of results compared to previous analyses, which were based on simplifying assumptions. We show that a combined merchant-regulatory regulation, which draws on a cap over the two-part tariff of the Transco, leads to welfare outcomes far superior to the modeled alternatives. This result proves to be robust over a range of different cases and sensitivity analyses. We also find that the intertemporal rebalancing of the two-part tariff carried out by the Transco so as to expand the network is such that the fixed tariff part turns out to be relatively large compared to extension costs.
Keywords: Q40; L51; D42; 330; electricity; regulation; transmission expansion; wind power